2023
DOI: 10.1186/s12889-023-16798-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of community based nutritional education on knowledge, attitude and compliance to IFA supplementation among pregnant women in rural areas of southwest Ethiopia: a quasi experimental study

Diriba Kumara Abdisa,
Debela Dereje Jaleta,
Dereje Tsegaye
et al.

Abstract: Background Compliance with the iron folic acid supplementation is low and not at the required level to prevent anaemia during pregnancy in many countries, including Ethiopia, even though an iron-folic acid supplementation program is being implemented. The aims of this study were to determine the effect of community-based nutritional education on knowledge, attitude, and compliance to IFA supplementation in Ilu Aba Bor zone of southwest Ethiopia. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The ndings of the present study show that the odds of adherence to IFAS were 2.3 times higher among those women who received nutrition education than those who did not. This nding is in agreement with studies conducted in Kenya and Ethiopia which resulted in improved adherence to IFAS among women who received education compared to the control group (17,20,41).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The ndings of the present study show that the odds of adherence to IFAS were 2.3 times higher among those women who received nutrition education than those who did not. This nding is in agreement with studies conducted in Kenya and Ethiopia which resulted in improved adherence to IFAS among women who received education compared to the control group (17,20,41).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by other studies conducted with the nutrition education and individual counseling in Nepal, Indonesia and India (29,31,37). Studies conducted by Abdisa et al and Berhane, et al showed that nutrition education and counseling during pregnancy can improved adherence to IFAS (17,18). A study by Araban et al also showed that nutritional education based on Health Belief Model increased iron and folic acid intake in pregnant women (38).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, it seems that efforts to acquire a balanced diet through good nutritional literacy are not sufficient, as reflected in the high rates of patients who come to a health center for care and do not receive the necessary preventive information [ 25 ]. Hence, it is important to take into account that contributing to a healthy society is everyone’s task, since, according to previous research, nutritional literacy symbolizes a significant change in people’s knowledge and attitudes [ 26 ]. Thus, it is important that in addition to health professionals, every individual can maintain a certain level of nutritional literacy in order to support disease prevention or combat diseases.…”
Section: Introductionmentioning
confidence: 99%